Coyuntura Económica - Aponte Jaramillo, Elizabeth; Palacio Salazar, Ivarth; Sánchez Rengifo, Holmes; Martínez Sandoval, Avelino; Vázquez Olave, Martha (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2005)
Coyuntura Económica